2018
DOI: 10.1186/s41232-018-0060-2
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced IL-34 expression in Nivolumab-resistant metastatic melanoma

Abstract: BackgroundImmunotherapies that target immune-checkpoint molecules such PD-1 have helped to achieve durable responses in melanoma treatment. However, 25% of melanoma patients who showed objective responses to PD-1 blockade develop resistance and suffer from disease progression and ultimately death, which necessitates the identification of related resistance mechanisms.IL-34 is a cytokine that controls the biology of myeloid cell lineage through binding to CSF-1R. IL-34 is importantly involved in the pathogenesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 30 publications
1
39
0
1
Order By: Relevance
“…16 Moreover, IL-34 expression is known to be associated with therapeutic resistance in lung cancer and melanoma. 33,36,37 Therefore, in this study, serum IL-34 level could reflect hepatic fibrosis as well as tumor factors, and was associated with the prognosis of patients with nonviral HCC.…”
Section: Discussionmentioning
confidence: 81%
“…16 Moreover, IL-34 expression is known to be associated with therapeutic resistance in lung cancer and melanoma. 33,36,37 Therefore, in this study, serum IL-34 level could reflect hepatic fibrosis as well as tumor factors, and was associated with the prognosis of patients with nonviral HCC.…”
Section: Discussionmentioning
confidence: 81%
“…Since IL‐34 is expressed at mRNA level in various tissues, this expression is expected to be changed under pathological conditions. Indeed, several studies have confirmed the enhancement of IL‐34 expression at mRNA and protein levels in the context of various diseases including autoimmune disorders, inflammation, infections, metabolic diseases, neurological disorders, and cancer . At the cellular level, IL‐34‐producing cells include synovial fibroblasts, immune cells, epithelial cells, endothelial cells, adipocytes, and cancer cells.…”
Section: Il‐34 Biologymentioning
confidence: 95%
“…CSF‐1R is expressed in a subset of cancer cells or can be induced upon exposure to chemotherapeutic agents . Similarly, IL‐34 is expressed in various types of cancer cells and can be induced by chemotherapy treatment . In an autocrine fashion, cancer cell‐derived IL‐34 induces strong activation of ERK1/2 and AKT downstream of CSF‐1R, thus providing CSF‐1R‐expressing cancer cells with a critical survival signaling that help them to survive under strict chemotherapeutic conditions, such as in pemetrexed‐treated pleural malignant mesothelioma cells, doxorubicin‐ or cisplatin‐treated lung cancer cells, and oxaliplatin‐treated colon cancer cells .…”
Section: Pathological Roles Of Il‐34mentioning
confidence: 99%
See 2 more Smart Citations